ANALISIS PENGARUH KAPASITANSI KAPASITOR TERHADAP TORSI, TEGANGAN, DAN ARUS PADA SISTEM PENGEREMAN REGENERATIF EKSITASI MANDIRI PADA MOTOR INDUKSI 3 FASA - teub elektro teub; Muhammad Rifqi Nur Sabilillah; Waru Djuriatno; Rini Nur Hasanah (Jurnal Mahasiswa TEUB, 2023)
The transportations have important role in facilitating population mobility, one of the transportations are the train. In order to decrease mass, speed up the movement, and decrease carbon emission, electrification has been done, so that electrical train was created. Three-phase induction motor is chosen as a mover because of its sturdiness, lack of brush and commutator, and also shock wave. Three-phase induction motor works using induction principle therefore the excitation can be obtained from stator induction to rotor. One of the most important parameters on the transportations is braking. Regenerative braking becomes an excellent option since it can obtain energy from braking process, it converts kinetic energy to electrical energy, in that case the motor act as a generator. It can occur when the slip is negative. Negative slip can be obtained when the synchronous speed is under the rotor speed. The testing to analyze capacitors capacitance for motor excitation is needed before applying to the real condition. The test has been done in two steps, there are noload test and loaded test using dc to dc converter and battery. The result from Simulink MATLAB 2022a simulation shows that the bigger capacitors capacitance, the lower regeneration frequency produced, so that the synchronous speed will be lower, then negative slip will be bigger that can inflict bigger braking torqueand bigger regeneration voltage. Keywords–– Capacitor Capacitance, Rotor Rotating Speed, Regeneration Voltage, Regenerative Braking, Synchronous Speed, Three-Phase Induction Motor, Torque